Regenerative endodontic procedures in immature permanent teeth with pulp necrosis: the impact of microbiology on clinical and radiographic outcome - Sellami, Rayann; Van Holm, Wannes; Meschi, Nastaran; Van Den Heuvel, Sarah; Pauwels, Martine; Verspecht, Tim; Vandamme, Kathleen; Teughels, Wim; Lambrechts, Paul (Frontiers in Dental Medicine, 2023)
Aims The current study aimed to determine how the disinfection strategy for regenerative endodontic procedures (REPs) influences overall bacterial load and REP outcomes. Different bacterial species in the teeth were also examined in this study. Methods A previously reported non-randomized controlled clinical research on REP ± leukocyte and platelet-rich fibrin gathered microbial samples from 14 of 29 patients during REP (LPRF). Four microbiological samples were obtained in two treatment sessions. S1 and S2 were taken before and after the first irrigation with 1.5% NaOCl and saline. Samples S3 and S4 were obtained before and after rinsing with 17% EDTA in the second treatment session. Microbial samples were identified using a quantitative polymerase chain reaction with species-specific primers. Results The total bacterial load recovered from patients showed a significant (p < 0.05) decrease after the first treatment and was maintained throughout the second treatment. Fusobacterium nucleatum, Treponema denticola, and Enterococcus faecalis were the most prevalent species in root canals, detected in all analyzed cases (100%), followed by Prevotella intermedia and Tannerella forsythia, both in six of 14 (42.9%) cases. The presence of these abundant species was significantly reduced after sample S1 was obtained. Parvimonas micra was present in four of 14 (28.6%) cases and Actinomyces naeslundii in two of 14 (14.3%) cases. Filifactor alocis, Porphyromonas endodontalis, and Porphyromonas gingivalis were each detected in only one of 14 (7.1%) cases. No statistical correlation could be made between bacterial species and clinical or radiographic outcomes due to the small sample size. In the LPRF group, two cases required retreatment due to early post-treatment flare-up, and two other cases presented radiographically presented a persistent apical periodontitis 3 years after treatment. In the control group, all analyzed cases were clinically asymptomatic after treatment, and radiographically, the final periapical index score at the last recall revealed healthy periapices. Conclusion The REP disinfection protocol of the present study seems to be satisfactorily effective in reducing the total bacterial load, omitting clinical symptoms and inducing periapical bone healing in immature permanent teeth with pulp necrosis. However, LPRF seems to prevent these outcomes from being achieved and should consequently therefore not be recommended in REPs.